Experimental investigation on the hydrodynamic performance of a quay moored jackup. (4th July 2017) - Liu, Lei; Yang, Jianmin; Tian, Xinliang; Lu, Haining; Li, Chunhui; Yuan, Hongtao
Abstract: Offshore platforms under construction are normally moored along the quayside during the outfitting stage. The safety of the platforms must be guaranteed during the entire process of outfitting which may last for several months. In this study, the hydrodynamic performance of a quay moored jackup is investigated by using a set of wave basin model tests. In the seakeeping model tests, the dynamic responses of the system, including the six degrees of freedom motions of the jackup and the barge, tensions on the mooring lines and the collision forces on the fenders, were measured in various sea states, and statistical analyses were conducted. Meanwhile, the dynamic responses in current-and-wind-only sea states were analysed for comparison with those in the wave conditions to assess the influence of the wind and the current. It is observed that the offshore wind plays an important role in quay mooring systems and the mooring line tensions are found to exceed the strength of the lines in offshore wind conditions. The possible reasons are discussed in detail and suggestions are proposed for optimising the mooring system performance.